2008
DOI: 10.1371/journal.pone.0001958
|View full text |Cite
|
Sign up to set email alerts
|

HDAC Inhibitors Correct Frataxin Deficiency in a Friedreich Ataxia Mouse Model

Abstract: BackgroundFriedreich ataxia, an autosomal recessive neurodegenerative and cardiac disease, is caused by abnormally low levels of frataxin, an essential mitochondrial protein. All Friedreich ataxia patients carry a GAA⋅TTC repeat expansion in the first intron of the frataxin gene, either in the homozygous state or in compound heterozygosity with other loss-of-function mutations. The GAA expansion inhibits frataxin expression through a heterochromatin-mediated repression mechanism. Histone modifications that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
200
4
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(221 citation statements)
references
References 29 publications
15
200
4
2
Order By: Relevance
“…These positive data were supported by other studies using in vivo models, with most mice responding favorably to treatment protocols incorporating HDACi (29,37).…”
Section: Hdac Inhibitor Activity In Mrtsupporting
confidence: 61%
“…These positive data were supported by other studies using in vivo models, with most mice responding favorably to treatment protocols incorporating HDACi (29,37).…”
Section: Hdac Inhibitor Activity In Mrtsupporting
confidence: 61%
“…Recently, mouse models for spinocerebellar ataxia 1 and Friedreich ataxia have led to potential drug targets and clinical trials. 4,5 In the future, this zebrafish model may also be used to understand the function of C19L1, analyze and confirm cell experiments, and ultimately test potential therapies for this form of ataxia.…”
Section: Results Exome Sequencing Identifies Mutation Inmentioning
confidence: 99%
“…Identifying additional recessive ataxia genes may help in diagnosis and prognosis and the identification of novel ataxia pathways, 3 which in turn may lead subsequently to novel drug development. 4,5 Next-generation sequencing has recently been used to identify genes involved in rare neurologic disorders, 6 including ataxia, 2,7-9 often with the help of consanguinity, 2 as homozygosity further narrows down the linkage evidence, 10 and homozygous mutations are easier to detect than 2 compound heterozygotes. Here, we identified a novel splice mutation by next-generation sequencing and homozygosity mapping in a small consanguineous family that leads to ataxia, developmental delay, and mental retardation in humans, and abnormalities in cerebellar morphology and movement in a zebrafish model with the same splicing defect.…”
mentioning
confidence: 99%
“…Toxicity studies of various HDAC inhibitors, including SAHA, have demonstrated widespread effects in human cancer cells in vitro, including activation of proapoptotic and inhibition of antiapoptotic pathways, stimulation of cell differentiation, and induction of growth arrest (20)(21)(22). These features have led to the approval of SAHA for use in human cancer clinical trials (22); however, such properties might be expected to exacerbate symptoms in neurodegenerative disorders, such as HD.We have developed a class of benzamide-type HDAC inhibitors that show promising results in Friedreich's ataxia disease models (23,24). These compounds are structurally related to the well-known HDAC inhibitor SAHA but are not hydroxamic acids and, unlike SAHA, were found to increase expression of the frataxin gene in lymphocytes from Friedreich's ataxia patients (23).…”
mentioning
confidence: 99%
“…We have developed a class of benzamide-type HDAC inhibitors that show promising results in Friedreich's ataxia disease models (23,24). These compounds are structurally related to the well-known HDAC inhibitor SAHA but are not hydroxamic acids and, unlike SAHA, were found to increase expression of the frataxin gene in lymphocytes from Friedreich's ataxia patients (23).…”
mentioning
confidence: 99%